Pursuing Flawless Experience Starts with the Adjustment of the Visual Layout: ATM Cardless Cash Withdrawal Services Study - Meng-Cong Zheng; Joon Ming Nigell Lay; Ching-I Chen (SAGE Open)
Self-service technology is widely used in the financial sector to ensure consumers can easily conduct financial transactions. For example, banks have successfully applied cardless withdrawal services to ATMs. However, many factors still exist as to why cardless withdrawals cannot be widely promoted. In the preliminary investigation work of this study, we investigated the user experience design of cardless cash withdrawals of the top three banks in Taiwan’s ATM market share. After summarizing many problems, we optimized the design to include two sets of typography and guidance. We used the task-oriented cognitive walkthrough method to survey 36 participants and adopted post-task and post-session self-report assessments, such as SEQ, NASA-TLX, satisfaction, preference, NPS, etc. Finally, it is supplemented by semi-structured interviews to understand users’ performance, thoughts, and problems when completing relevant tasks. It was found that users with different experiences have different needs for the interface, which are reflected in different workload items. In addition, the correlation between the scales was discovered, and suggestions were provided for future industry workers who want to practice data-driven UX.